Seizing the moment: communicating ethics, decisions, and neurotechnological approaches to pediatric drug-resistant epilepsy - Illes, Judy; McDonald, Patrick J.; Ibrahim, George M.; Connolly, Mary B.; Naftel, Robert P.; Bacani, Marianne; Nuechterlein, Anna; Go, Samantha P.; Roduit, Johann (Frontiers in Communication, 2024)
It is a fundamental duty of neuroscientists to discuss the results of research and related ethical implications. Engagement with neuroscience is especially critical for families with children affected by disorders such as drug resistant epilepsy (DRE) as they navigate complex decisions about innovations in treatment that increasingly include invasive neurotechnologies. Through an evidencebased, iterative, and value-guided approach, we created the short-form documentary film, Seizing Hope: High Tech Journeys in Pediatric Epilepsy, to delve into the relationship between experts with first-hand, lived experience -youth with DRE and caregivers -and physician experts as they weigh medical and ethical trade-offs on this landscape. We describe the co-creation and evolution of this film, screenings, and feedback. Survey responses from 385 viewers highlight new developments in technologies for the treatment of DRE, how families navigate choices for treatment with brain technology, and a sense of hope for the future for children with epilepsy as key attributes of this science communication piece.